2006
DOI: 10.1007/s11030-005-9013-1
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Homemade Reaction Station for use in Parallel Solution-Phase Synthesis. Optimization of a Regioselective One-Step Deprotective o-formylation Reaction Mediated by the Vilsmeier-Haack Reagent POCl3⋅DMF

Abstract: We report herein the fabrication of a simple and price-affordable portable reaction station for use in parallel solution-phase synthesis. This homemade device uses currently available laboratory components and equipment. Specifically designed to fit standard magnetic hotplates/stirrers, it can simultaneously hold up to 24 heated and magnetically stirred glass reactors of both 10 and 50 mL capacities. Glass reactors are connected by flexible 16-gauge metal needles to a central gas manifold equipped with an inle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Herewith now we report the selective formylation of phenols promoted by metal ions under V-H conditions. Nevertheless, in one of the earlier reports metal ions in conjunction with DMF/POCl 3 have been used for one step deprotective O-formylation of bis-O-tertiary butyl diphenyl silyl (O-TBDPS) aromatic diol [28].…”
Section: Resultsmentioning
confidence: 99%
“…Herewith now we report the selective formylation of phenols promoted by metal ions under V-H conditions. Nevertheless, in one of the earlier reports metal ions in conjunction with DMF/POCl 3 have been used for one step deprotective O-formylation of bis-O-tertiary butyl diphenyl silyl (O-TBDPS) aromatic diol [28].…”
Section: Resultsmentioning
confidence: 99%
“…76 In 2006, Kotlyar et al reported the Vilsmeier-Haackmediated O-formylation of the sterically hindered bis-Otert-butyldiphenylsilyl (O-TBDPS) aromatic diol 155 using a range of Lewis acids and metal salt promoters to give product 156 (Scheme 46). 77 The reaction proceeded efficiently and product 156 was obtained in 79% yield.…”
Section: Ortho-formylationmentioning
confidence: 98%
“…[2] A more compelling alternative method for the synthesis of formate ester derivatives is via an O-alkylation of amides with alkyl halides. [3] Reports that exploit dimethylformamide (DMF) as a formate anion equivalent in the synthesis of formate ester have also been revealed.…”
Section: Introductionmentioning
confidence: 99%